Method for grain boundary diffusion strengthening of neodymium-iron-boron magnets and grain boundary strengthened neodymium-iron-boron magnets

CN117637332BActive Publication Date: 2026-10-23NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311758983.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-10-23
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

然而,由于扩散服从菲克定律,扩散的驱动力来源于浓度梯度,使得晶界扩散技术通常只适用于薄块或小尺寸磁体,不利于扩散磁体的应用发展

Benefits of technology

[0018]与现有技术相比,本发明的有益效果至少在于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117637332B_ABST
    Figure CN117637332B_ABST
Patent Text Reader

Abstract

The application discloses a method for strengthening a neodymium-iron-boron magnet by grain boundary diffusion and a grain boundary strengthened neodymium-iron-boron magnet. The method comprises the following steps: applying a first diffusion source to the surface of a neodymium-iron-boron magnet and performing low-temperature grain boundary diffusion treatment; applying a second diffusion source to the surface of the neodymium-iron-boron magnet after the low-temperature grain boundary diffusion treatment and performing medium-temperature grain boundary diffusion treatment; applying a third diffusion source to the surface of the neodymium-iron-boron magnet after the medium-temperature grain boundary diffusion treatment and performing high-temperature grain boundary diffusion treatment; the content of heavy rare earth elements in the first diffusion source, the second diffusion source and the third diffusion source increases in sequence; finally, annealing treatment is performed to obtain the grain boundary strengthened neodymium-iron-boron magnet. The method for strengthening the neodymium-iron-boron magnet by grain boundary diffusion in the application adopts a multiple grain boundary diffusion treatment mode for regulating the content of heavy rare earth elements, adjusts the microstructure in the magnet in a targeted manner, effectively improves the utilization rate of heavy rare earth elements, strengthens the coercive force of the magnet, and the method is suitable for batch diffusion modification of large-size magnets and has good consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rare earth permanent magnet materials technology, and specifically relates to a method for grain boundary diffusion-strengthened NdFeB magnets, and the obtained grain boundary-strengthened NdFeB magnets. Background Technology

[0002] Neodymium iron boron (NdFeB) rare-earth permanent magnet materials are widely used in high-tech fields such as new energy vehicles, rail transportation, and wind power generation. However, their poor magnetic properties and temperature stability severely restrict the further expansion of NdFeB's application areas. Improving coercivity (H) cj Temperature stability is an effective way to improve magnetic properties. Given that the actual coercivity of NdFeB magnets is less than 30% of the theoretical value, improving coercivity is of great significance. The empirical formula for the coercivity of NdFeB magnets is as follows:

[0003] H cj =α·H A -N eff ·M s

[0004] Wherein, α is the coercivity coefficient factor, which is related to the microstructure of the magnet; the stronger the magnetic isolation effect of the grain boundaries and the fewer the surface defects of the grains, the larger α is; H A It is a magnetocrystalline anisotropic field, which is related to the composition of the magnet. Introducing heavy rare earth elements into the main phase can significantly enhance H. A N eff It is the effective demagnetizing factor, mainly related to the macroscopic dimensions of the magnet; M s It is the saturation magnetization, which is related to the intrinsic components of the magnet. Clearly, increasing α and H... A It is the most effective way to improve the coercivity of magnets.

[0005] Grain boundary diffusion technology can achieve the diffusion of α and H atoms on the surface of a magnet. A The principle behind increasing the Hg is to attach rare-earth-containing elements or compounds to the magnet surface. Through a specific heat treatment process, the attached material diffuses along grain boundary channels into the magnet's interior, widening the grain boundaries and repairing surface defects. (If the attached material contains heavy rare-earth elements, it will also significantly increase the Hg of the epitaxial layer.) A This significantly improves the coercivity of the magnet. However, since diffusion obeys Fick's law and the driving force for diffusion comes from the concentration gradient, grain boundary diffusion technology is usually only applicable to thin or small-sized magnets, which is not conducive to the development of diffused magnet applications. Studies have shown that as the proportion of heavy rare earth elements in the rare earth component of the diffused deposit decreases, the diffusion depth of the deposit can be effectively increased. At the same time, the magnetic isolation effect of grain boundaries within the diffusion depth range increases significantly (α increases significantly), but the strengthening effect of the epitaxial layer of grains within this depth range decreases significantly (H). AThe strengthening effect is reduced, which means that it is difficult to achieve diffusion strengthening effect on larger NdFeB magnets by simply adjusting the composition ratio of the diffuser.

[0006] Recent practice has revealed that the near-surface layer of magnets contains numerous microscopic defects due to sintering, rapid cooling, and machining processes, with the number of defects gradually decreasing with increasing depth. Simultaneously, because the self-demagnetizing effect near the magnet's surface is significantly greater than that inside, simply increasing the magnetic isolation of grain boundaries on the magnet's surface is insufficient to effectively suppress the expansion of demagnetization domains. Therefore, increasing the H0 of the magnet's surface layer is crucial. A Strengthening the internal α layer of the magnet is an essential choice for magnet enhancement, and the enhancement should be targeted at both the internal and surface layers. Furthermore, given the scarcity and high price of heavy rare earth resources, further promoting the upgrading of low-heavy rare earth diffusion technology to achieve efficient utilization of heavy rare earths and realize comprehensive diffusion strengthening of large-size magnets is of great significance to the development of NdFeB permanent magnet materials. Summary of the Invention

[0007] The main objective of this invention is to provide a method for producing a grain boundary diffusion-strengthened NdFeB magnet and the resulting grain boundary-strengthened NdFeB magnet, thereby overcoming the shortcomings of the prior art.

[0008] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0009] This invention provides a method for strengthening NdFeB magnets through grain boundary diffusion, comprising:

[0010] A first diffusion source is provided and applied to the surface of a neodymium iron boron magnet, followed by low-temperature grain boundary diffusion treatment;

[0011] A second diffusion source is provided and applied to the surface of a neodymium iron boron magnet that has undergone low-temperature grain boundary diffusion treatment, followed by medium-temperature grain boundary diffusion treatment;

[0012] A third diffusion source is provided and applied to the surface of a neodymium iron boron magnet after medium-temperature grain boundary diffusion treatment, followed by high-temperature grain boundary diffusion treatment; wherein the content of heavy rare earth elements in the first diffusion source, the second diffusion source and the third diffusion source increases sequentially;

[0013] Grain boundary strengthened NdFeB magnets were obtained by annealing NdFeB magnets that had undergone high-temperature grain boundary diffusion treatment.

[0014] In some preferred embodiments, the process conditions for the low-temperature grain boundary diffusion treatment include: a diffusion temperature of 800–900°C, a holding time of 4–20 h, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0015] In some preferred embodiments, the process conditions for the intermediate-temperature grain boundary diffusion treatment include: a diffusion temperature of 850–950°C, a holding time of 2–10 h, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0016] In some preferred embodiments, the process conditions for the high-temperature grain boundary diffusion treatment include: a diffusion temperature of 900–1000°C, a holding time of 2–4 hours, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0017] In some preferred embodiments, the annealing process conditions include: an annealing temperature of 400–600°C, a holding time of 1–10 h, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0018] Compared with the prior art, the beneficial effects of the present invention are at least as follows:

[0019] The method for strengthening NdFeB magnets through grain boundary diffusion provided by this invention employs a multi-stage grain boundary diffusion treatment with controlled heavy rare earth content. Compared with the traditional single-step diffusion, this method specifically adjusts the microstructure inside the magnet. This invention effectively utilizes the diffusion mechanism of various elements on the magnet, ensuring the strengthening effect while reducing the amount of heavy rare earth used by designing different diffusion source ratios. This effectively improves the utilization efficiency of heavy rare earth, meaning less heavy rare earth is used and the utilization efficiency is increased, thus strengthening the coercivity of the magnet. Furthermore, the magnets strengthened by diffusion according to this invention exhibit good performance stability and consistency, making them suitable for the mass diffusion modification production of large-size magnets. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of a method for strengthening NdFeB magnets through grain boundary diffusion in a typical embodiment of the present invention.

[0022] Figure 2a and Figure 2b The images show elemental distribution maps (EPMA maps) of a magnet prepared using a typical embodiment of the present invention and a magnet prepared using a conventional method. Detailed Implementation

[0023] In view of the shortcomings of the prior art, in order to achieve grain boundary strengthening modification of large-size NdFeB magnets and efficient utilization of heavy rare earth resources, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The method for grain boundary diffusion strengthening of NdFeB magnets proposed in this invention is based on extensive and long-term practice. To further understand this invention, the technical solution, its implementation process, and principles will be further explained below. However, it should be understood that these descriptions are only for further illustrating the features and advantages of this invention, and not for limiting the scope of the claims.

[0024] One aspect of the present invention provides a method for grain boundary diffusion-strengthened NdFeB magnets, comprising:

[0025] A first diffusion source is provided and applied to the surface of a neodymium iron boron magnet, followed by low-temperature grain boundary diffusion treatment;

[0026] A second diffusion source is provided and applied to the surface of a neodymium iron boron magnet after low-temperature grain boundary diffusion treatment, followed by medium-temperature grain boundary diffusion treatment;

[0027] A third diffusion source is provided and applied to the surface of a neodymium iron boron magnet after medium-temperature grain boundary diffusion treatment, followed by high-temperature grain boundary diffusion treatment; wherein the content of heavy rare earth elements in the first diffusion source, the second diffusion source and the third diffusion source increases sequentially;

[0028] Annealing was performed on NdFeB magnets that had undergone high-temperature grain boundary diffusion treatment to obtain grain boundary strengthened NdFeB magnets.

[0029] In some preferred embodiments of the present invention, please refer to Figure 1 As shown, a method for strengthening NdFeB magnets through grain boundary diffusion includes the following steps:

[0030] Step 1: Prepare diffusion source A with low heavy rare earth content (i.e., the first diffusion source mentioned above), attach diffusion source A to the surface of sintered NdFeB magnet, and perform low-temperature grain boundary diffusion treatment on it to preliminarily modify the grain boundary distribution inside the entire magnet.

[0031] Step 2: Prepare diffusion source B with a suitable heavy rare earth content (i.e., the aforementioned second diffusion source), and attach diffusion source B to the surface of the NdFeB magnet obtained after step 1, and perform medium-temperature grain boundary diffusion treatment on it.

[0032] Step 3: Prepare diffusion source C with a high content of heavy rare earth elements (i.e., the aforementioned third diffusion source), and attach diffusion source C to the surface of the neodymium iron boron magnet obtained after step 2, and perform high-temperature grain boundary diffusion treatment on it.

[0033] Step 4: Anneal the NdFeB magnet obtained in Step 3 to obtain a grain boundary strengthened NdFeB magnet.

[0034] Under current production technology, magnets produced often have various internal defects, limiting performance improvement. This invention creatively addresses two problems that lead to insufficient magnet performance: uneven grain boundary distribution and numerous microscopic defects near the surface. First, a diffusion source with low heavy rare earth content is designed and grain boundary diffusion is performed to enhance demagnetization coupling and optimize grain boundary phase distribution within the magnet. Next, a diffusion source with moderate heavy rare earth content is designed and grain boundary diffusion is performed again to enhance the magnet's surface resistance to demagnetization. Finally, a diffusion source with high heavy rare earth content is designed and grain boundary diffusion is performed to significantly enhance magnetohardening near the surface and suppress self-demagnetization caused by processing defects. The technical solution proposed in this invention utilizes the different diffusion capabilities and strengthening effects of diffusion sources with different heavy rare earth contents (diffusion sources with low heavy rare earth contents have a deeper diffusion depth, which can significantly optimize grain boundaries and improve the demagnetization coupling capability of grain boundaries; diffusion sources with moderate heavy rare earth contents have slightly weaker diffusion capabilities, which can achieve the dual effects of grain magnetic hardening and grain boundary demagnetization coupling; diffusion sources with high heavy rare earth contents have poor diffusion capabilities, but can greatly enhance the magnetic hardening effect of grains and significantly suppress the self-demagnetization behavior of grain surface layers. After three steps of targeted grain boundary diffusion strengthening of different depth weak areas of the magnet, the performance improvement of the magnet is more significant).

[0035] In some implementation schemes, in steps one, two, and three, the preparation process of the three diffusion sources A (i.e., the aforementioned first diffusion source), B (i.e., the aforementioned second diffusion source), and C (i.e., the aforementioned third diffusion source) is as follows: raw materials are prepared according to mass percentage, and alloy is smelted in a rapid solidification furnace. The obtained rapid solidification flakes are then hydrogen-crushed into coarse powder, and the coarse powder is then milled by air jet milling to obtain fine powder with a particle size distribution of 2 to 50 micrometers. This fine powder is the powdered diffusion source, thus obtaining the first diffusion source, the second diffusion source, or the third diffusion source.

[0036] In some implementations, steps one, two, and three include: applying and attaching the first, second, or third diffusion source to the surface of the NdFeB magnet by at least one of the following methods: spraying, slurry impregnation, or screen printing. That is, the attachment methods for the three diffusion sources (first, second, and third) can include spraying, slurry impregnation, screen printing, etc., and the amount of diffusion source attached must meet certain requirements.

[0037] Furthermore, the amount of the first diffusion source attached to the surface of the NdFeB magnet in step one is 1-3% (mass percentage).

[0038] Furthermore, the amount of the second diffusion source attached to the surface of the NdFeB magnet in step two is 1-2% (mass percentage).

[0039] Furthermore, the amount of the third diffusion source in step three attached to the surface of the NdFeB magnet is 0.3–0.8% (mass percentage).

[0040] In some implementation schemes, in step one, the sintered NdFeB magnet can be selected from conventional models such as N35, N38, N40, N42, N45, N48, N50, N52, and N55, with a magnet thickness of 2 to 15 mm.

[0041] In some preferred embodiments of the present invention, in step one, the chemical formula of the first diffusion source (i.e., diffusion source A with a low heavy rare earth content) is RE1 by mass percentage. a RE2 b M 100-a-b RE1 includes any one or more combinations of terbium (Tb), dysprosium (Dy), and holmium (Ho); RE2 includes any one or more combinations of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), and samarium (Sm); M is a non-ferrous metal, preferably including any one or more combinations of common non-ferrous metals such as magnesium (Mg), aluminum (Al), cobalt (Co), copper (Cu), and gallium (Ga), and satisfies 0≤a≤5 and 50≤b≤95.

[0042] In some preferred embodiments of the present invention, in step one, the process conditions for the low-temperature grain boundary diffusion treatment include: a diffusion temperature of 800–900°C, a holding time of 4–20 h, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0043] In some preferred embodiments of the present invention, in step two, the chemical formula of the second diffusion source (i.e., diffusion source B with a suitable heavy rare earth content) is REl by mass percentage. m RE2 n M 100-m-n RE1 includes any one or more combinations of terbium (Tb), dysprosium (Dy), and holmium (Ho); RE2 includes any one or more combinations of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), and samarium (Sm); M is a non-ferrous metal, preferably including any one or more combinations of common non-ferrous metals such as magnesium (Mg), aluminum (Al), cobalt (Co), copper (Cu), and gallium (Ga), and satisfies 25≤m≤50 and 25≤n≤50.

[0044] In some preferred embodiments of the present invention, in step two, the process conditions for the intermediate-temperature grain boundary diffusion treatment include: a diffusion temperature of 850–950°C, a holding time of 2–10 h, and a vacuum degree not exceeding 1 × 10⁻⁶.-2 Pa.

[0045] In some preferred embodiments of the present invention, in step three, the chemical formula of the third diffusion source (i.e., diffusion source C with a high content of heavy rare earth elements) is RE1. i RE2 j NRE q In this invention, RE1 includes any one or more combinations of terbium (Tb), dysprosium (Dy), and holmium (Ho); RE2 includes any one or more combinations of lanthanum (La), cerium (Ce), praseodymium (UPr), neodymium (Nd), and samarium (Sm); and NRE is a high-melting-point metal, preferably including any one or more combinations of high-melting-point metals such as tungsten (W), molybdenum (Mo), niobium (Nb), tantalum (Ta), vanadium (V), and zirconium (Zr), satisfying i≥80, 0≤j≤10, 0≤q≤10, and i+j+q=100. The high-heavy rare-earth content diffusion source in the third step of this invention, combined with high-melting-point metals, can effectively magnetize the surface grains while increasing the corrosion resistance and other properties of the magnet surface, significantly improving the magnet's service performance.

[0046] In some preferred embodiments of the present invention, in step three, the process conditions for the high-temperature grain boundary diffusion treatment include: a diffusion temperature of 900–1000°C, a holding time of 2–4 hours, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0047] In some preferred embodiments of the present invention, in step four, the annealing process conditions include: an annealing temperature of 400–600°C, a holding time of 1–10 h, and a vacuum degree not exceeding 1 × 10⁻⁶. -2 Pa.

[0048] In this invention, the first diffusion process has a high content of light rare earth and non-rare earth elements, which effectively penetrates and widens the grain boundaries, and the depth of action is superior to most current diffusion processes. The second and third diffusion processes gradually increase the amount of heavy rare earth elements, which gradually solves the strong self-demagnetization phenomenon near the surface while ensuring the diffusion depth. Therefore, this invention is suitable for thicker, large-size magnets and can achieve diffusion-enhanced modification of large-size magnets.

[0049] This invention effectively utilizes the diffusion mechanism of various elements on magnets, ensuring the enhancement effect on magnets while reducing the amount of heavy rare earth elements used by designing different diffusion source ratios, thereby improving the utilization efficiency of heavy rare earth elements. In other words, less heavy rare earth elements are used and the utilization efficiency is improved.

[0050] Another aspect of this invention provides a grain boundary-strengthened NdFeB magnet prepared by the method described above. The diffusion-strengthened magnet of this invention exhibits good performance stability and consistency, making it suitable for mass production.

[0051] In summary, this invention employs a multi-grain boundary diffusion treatment method that regulates the content of heavy rare earth elements. Compared with the traditional single-step diffusion, this method specifically adjusts the microstructure inside the magnet, effectively improving the utilization rate of heavy rare earth elements and enhancing the coercivity of the magnet. Furthermore, this invention is suitable for the batch diffusion modification of large-size magnets and exhibits good consistency.

[0052] To further illustrate the present invention, the technical solutions of the present invention are described in detail below with reference to the embodiments. However, it should be understood that these embodiments are implemented under the premise of the technical solutions of the present invention, and detailed implementation methods and specific operation processes are given. They are only for further illustrating the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0053] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0054] There are no particular restrictions on the purity of any of the raw materials used in this invention. However, this invention preferably uses industrial-grade pure materials or materials with conventional purity used in the preparation of electroplated coatings on the surface of NdFeB magnets.

[0055] All processes and equipment in this invention are conventional names in the field, and each name is clear and unambiguous in its relevant application. Those skilled in the art can understand the conventional process steps and corresponding equipment used based on the name.

[0056] Example 1

[0057] Commercially available NdFeB magnets of grade N55 were used as the diffusion substrate. The magnet thickness was machined to 8 mm, and the surface was cleaned before use. Dy5Nd was applied by weight percentage. 75 Cu 20 Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder A with a particle size distribution of 2 micrometers. 2.7% by mass of diffusion source fine powder A was sprayed onto the surface of the diffusion matrix and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 900℃ and held for 16 hours. After rapid cooling to room temperature, the magnet was removed to obtain the initial diffusion magnet; Dy was calculated by mass percentage. 25 Pr 25 Co 50 Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder B with a particle size distribution of 2.5 micrometers. 1.4% by mass of diffusion source fine powder B was sprayed onto the surface of the initial diffusion magnet, and the magnet was placed under a vacuum of 3 × 10⁻⁶. - 3In a vacuum melting furnace of Pa, the temperature was raised to 950℃ and held for 10 hours. After rapid cooling to room temperature, the magnet was removed to obtain a re-diffused magnet; Dy was calculated by mass percentage. 90 Nb5Zr5 alloy was smelted and rapidly solidified to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder C with a particle size distribution of 3 micrometers. 0.5% by mass of diffusion source fine powder C was sprayed onto the surface of a diffusion magnet and placed under a vacuum of 3×10⁻⁶. -3 The magnet was heated to 1000℃ and held for 4 hours in a vacuum melting furnace with a pressure of Pa. After rapid cooling to room temperature, it was removed to obtain a fully diffused magnet. The fully diffused magnet was then placed in a vacuum of 3×10⁻⁶ Pa. -3 In a vacuum melting furnace, the magnet was heated to 600℃ and held for 2 hours for annealing. After rapid cooling to room temperature, it was removed to obtain the target magnet 1#. To highlight the diffusion effect of this invention, a conventional DyHx diffusion source was used for diffusion, and the diffusion temperature was selected using a conventional process (diffusion at 900℃ for 12 hours, annealing at 500℃ for 4 hours) to prepare parallel sample 1#. The performance of the original N55 magnet, the target magnet 1#, and the parallel sample 1# is shown in Table 1 below.

[0058] Table 1 Comparison of magnetic properties of the original N55 magnet, target magnet #1, and parallel sample #1

[0059] N55 13.2 14.6 53.8 / Target Magnet #1 23.8 14.3 49.3 10.6 Parallel Sample 1# 19.2 14.2 48.2 6.0

[0060] Table 1 shows that the technical solution of this invention achieves a greater increase in coercivity and higher magnet performance. Furthermore, elemental distribution detection (EPMA analysis) was performed on the target magnet 1# and parallel sample 1# to observe their elemental distribution characteristics. The distribution results of the heavy rare earth element Dy are as follows: Figure 2a and Figure 2b As shown ( Figure 2a -Target magnet 1# prepared by the technical solution of this invention; Figure 2b - Parallel sample 1# prepared by conventional DyHx diffusion, from Figure 2a As can be seen from the technical solution proposed in this invention, a layered strengthening structure that is beneficial to magnetic properties can be constructed, avoiding the accumulation of heavy rare earth Dy on the surface of the magnet and improving the utilization rate of heavy rare earth.

[0061] Example 2

[0062] Commercially available sintered NdFeB magnets of grade 52M were used as the diffusion substrate. The magnet thickness was machined to 10 mm, and the surface was cleaned before use. Tb3Pr was added by weight percentage. 77 Cu 10 Al 10Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder A with a particle size distribution of 5 micrometers. 2.4% by mass of diffusion source fine powder A was sprayed onto the surface of the diffusion matrix and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 900℃ and held for 12 hours. After rapid cooling to room temperature, the magnet was removed to obtain a primary diffusion magnet. The surface of the primary diffusion magnet was polished and then mixed with alcohol at a mass percentage of Tb. 40 Pr 40 Cu 10 Al 10 Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder B with a particle size distribution of 4 micrometers. 1.4% by mass of diffusion source fine powder B was sprayed onto the surface of the initial diffusion magnet, and the magnet was placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 950℃ and held for 6 hours. After rapid cooling to room temperature, the magnet was removed to obtain a re-diffusion magnet. Tb was then added according to mass percentage. 80 Pr 1s Nb5 alloy was melted and rapidly solidified to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder C with a particle size distribution of 5 micrometers. 0.4% by mass of diffusion source fine powder C was sprayed onto the surface of a diffusion magnet and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace, the temperature was raised to 1000℃ and held for 2 hours. After rapid cooling to room temperature, the magnet was removed to obtain a fully diffused magnet. The fully diffused magnet was then placed in a vacuum of 3×10⁻⁶. -3 In a vacuum melting furnace, the temperature was raised to 600°C and held for 2 hours for annealing. After rapid cooling to room temperature, the magnet was removed to obtain target magnet #2. To highlight the diffusion effect of this invention, conventional TbH was used. x The diffusion source was used for diffusion, and the diffusion temperature was selected using conventional processes (diffusion at 900℃ for 12 hours, annealing at 500℃ for 4 hours) to prepare parallel sample 2#. The performance of the original 52M magnet, the target magnet 2#, and the parallel sample 2# is shown in Table 2 below.

[0063] Table 2 Comparison of magnetic properties of the original 52M magnet, target magnet #2, and parallel sample #2

[0064]

[0065]

[0066] As shown in Table 2, the coercivity is increased more significantly and the magnet performance is higher when the technical solution of the present invention is adopted.

[0067] Comparative Example 1

[0068] A control experiment was set up to treat commercially available N55 sintered NdFeB magnets, and the composition of diffusion source A was modified by mass percentage to Dy. 10 Nd 70 Cu 20 Other processing steps were the same as in Example 1, and comparative sample 1-01 was finally obtained.

[0069] A control experiment was set up to treat commercially available NdFeB magnets of grade N55, and the composition of diffusion source B was modified to Dy by mass percentage. 20 Nd 30 Co 50 Other processing steps were the same as in Example 1, and comparative sample 1-02 was finally obtained.

[0070] A control experiment was set up to treat commercially available NdFeB magnets of grade N55, and the composition of diffusion source B was modified to Dy by mass percentage. 55 Nd 45 Other processing steps were the same as in Example 1, and comparative sample 1-03 was finally obtained.

[0071] A control experiment was set up to treat commercially available N55 sintered NdFeB magnets, and the composition of the diffusion source C was modified to Dy by mass percentage. 85 Nb 7.5 Zr 7.5 (The combined proportion of high-melting-point metals Nb and Zr is 15%, which is too high.) Other processing steps are the same as in Example 1, and finally, comparative sample 1-04 is obtained.

[0072] The performance of samples 1-01, 1-02, 1-03, and 1-04 is shown in Table 3 below.

[0073] Table 3 compares the performance of samples 1-01, 1-02, 1-03, and 1-04.

[0074] Comparison Sample 1-01 22.9 14.4 49.9 9.7 Comparison Sample 1-02 23.1 14.3 49.4 9.9 Comparison Sample 1-03 23.4 14.2 48.5 10.2 Comparison Sample 1-04 23.2 14.4 50.1 10.0

[0075] As can be seen from the results of Comparative Example 1, adjusting the composition range of diffusion sources A, B, and C to deviate from the composition range of the technical solution of this invention will reduce the increase in coercivity of the final magnet.

[0076] Comparative Example 2

[0077] A control experiment was set up to process commercially available NdFeB magnets of grade N55. Compared with Example 1, only the spraying and diffusion treatment of diffusion source A was completed (the treatment process was the same as in Example 1) to obtain the initial diffusion magnet, without subsequent attachment and diffusion of diffusion sources B and C; the initial diffusion magnet was annealed (the treatment process was the same as in Example 1) to finally obtain control sample 2-01;

[0078] A control experiment was set up to process commercially available NdFeB magnets of grade N55. Compared with Example 1, after the sequential attachment and diffusion treatment of diffusion source A and diffusion source B (the treatment process is the same as in Example 1), a re-diffused magnet was obtained, but the subsequent attachment and diffusion of diffusion source C was not performed. The re-diffused magnet was then annealed (the treatment process is the same as in Example 1) to finally obtain control sample 2-02.

[0079] A control experiment was set up to process commercially available NdFeB magnets of grade N55. Compared with Example 1, after completing the spraying and diffusion treatment of diffusion source A (the treatment process is the same as in Example 1), the attachment and diffusion of diffusion source B were not performed. Instead, the attachment and diffusion of diffusion source C were directly performed to obtain a re-diffused magnet. The re-diffused magnet was then annealed (the treatment process is the same as in Example 1) to finally obtain control sample 2-03.

[0080] A control experiment was set up to process a commercially available NdFeB magnet of grade N55. Compared with Example 1, no attachment and diffusion were performed with diffusion source A, but instead, attachment and diffusion were performed with diffusion sources B and C in sequence (the processing technology was the same as in Example 1). Then, annealing was performed (the processing technology was the same as in Example 1), and finally, control sample 2-04 was obtained.

[0081] The performance of samples 2-01, 2-02, 2-03, and 2-04 is shown in Table 4 below.

[0082] Table 4 compares the performance of samples 2-01, 2-02, 2-03, and 2-04.

[0083] Comparison Sample 2-01 16.8 14.5 50.8 3.6 Comparison Sample 2-02 22.5 14.4 49.9 9.3 Comparison sample 2-03 20.1 14.4 48.6 6.9 Comparison sample 2-04 19.8 14.3 49.5 6.6

[0084] As can be seen from the results of Comparative Example 2 and Example 1, using only diffusion source A or only using a combination of diffusion sources A and B, A and C, B and C, which deviates from the technical solution provided by the present invention, will reduce the performance of the magnet.

[0085] Comparative Example 3

[0086] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 2.7% by mass of diffusion source fine powder A was sprayed onto the surface of the diffusion substrate and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 700℃ and held for 16 hours. Other processing steps were the same as in Example 1, and finally comparative sample 3-01 was obtained.

[0087] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 2.7% by mass of diffusion source fine powder A was sprayed onto the surface of the diffusion substrate and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 1000℃ and held for 16 hours. Other processing steps were the same as in Example 1, and comparative sample 3-02 was finally obtained.

[0088] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 1.4% by mass of diffusion source fine powder B was sprayed onto the surface of the initial diffusion magnet, and it was placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 800℃ and held for 10 hours. Other processing steps were the same as in Example 1, and finally comparative sample 3-03 was obtained.

[0089] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 1.4% by mass of diffusion source fine powder B was sprayed onto the surface of the initial diffusion magnet, and it was placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 1000℃ and held for 10 hours. Other processing steps were the same as in Example 1, and comparative sample 3-04 was finally obtained.

[0090] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 0.5% by mass of diffusion source fine powder C was sprayed onto the surface of the diffusion magnet, and it was placed under a vacuum of 3×10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 850°C and held for 4 hours. Other processing steps were the same as in Example 1, and finally comparative sample 3-05 was obtained.

[0091] A control experiment was set up to treat commercially available NdFeB magnets of grade N55. Compared with Example 1, 0.5% by mass of diffusion source fine powder C was sprayed onto the surface of the diffusion magnet, and it was placed under a vacuum of 3×10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 1100℃ and held for 4 hours. Other processing steps were the same as in Example 1, and finally comparative sample 3-06 was obtained.

[0092] A control experiment was set up to process commercial NdFeB magnets of grade N55. Compared with Example 1, the annealing temperature was adjusted to 300℃, and other processing techniques were the same as in Example 1. Finally, the control sample 3-07 was obtained.

[0093] A control experiment was set up to process commercial NdFeB magnets of grade N55. Compared with Example 1, the annealing temperature was adjusted to 700℃, and other processing techniques were the same as in Example 1. Finally, control sample 3-08 was obtained.

[0094] The performance of samples 3-01, 3-02, 3-03, 3-04, 3-05, 3-06, 3-07, and 3-08 is shown in Table 5 below.

[0095] Table 5 compares the performance of samples 3-01, 3-02, 3-03, 3-04, 3-05, 3-06, 3-07, and 3-08.

[0096] Comparison Sample 3-01 19.9 14.3 49.9 6.7 Comparison sample 3-02 22.9 14.2 48.1 9.7 Comparison sample 3-03 21.8 14.3 49.8 8.6 Comparison sample 3-04 22.5 14.3 49.2 9.3 Comparison sample 3-05 22.9 14.4 50.1 9.7 Comparison sample 3-06 23.5 14.2 48.2 10.3 Comparison sample 3-07 22.5 14.3 49.3 9.3 Comparison sample 3-08 22.6 14.3 49.3 9.4

[0097] As can be seen from the results of Comparative Example 3 and Example 1, deviating the diffusion treatment or annealing temperature from the technical solution provided by the present invention will reduce the performance of the magnet.

[0098] Example 3

[0099] Commercially available sintered NdFeB magnets of grade 52H were used as the diffusion substrate. The magnet thickness was machined to 5 mm, and its surface was cleaned before use. Nd was added by weight percentage. 80 Ga 20 Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder A with a particle size distribution of 2 micrometers. 2.7% by mass of diffusion source fine powder A was sprayed onto the surface of the diffusion matrix and placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 900℃ and held for 16 hours. After rapid cooling to room temperature, the magnet was removed to obtain the initial diffusion magnet; Dy was calculated by mass percentage. 45 Ho 15 Pr 30 Ga 10 Alloy melting and rapid solidification were performed to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder B with a particle size distribution of 2.5 micrometers. 1.4% by mass of diffusion source fine powder B was sprayed onto the surface of the initial diffusion magnet, and the magnet was placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 950℃ and held for 10 hours. After rapid cooling to room temperature, the magnet was removed to obtain a re-diffusion magnet; Dy was calculated by mass percentage. 70 Ho 10 Pr 10 Nb5Mo5 alloy was smelted and rapidly solidified to obtain rapidly solidified flakes, which were then hydrogen-crushed and air-jet milled to obtain diffusion source fine powder C with a particle size distribution of 3 micrometers. 0.5% by mass of diffusion source fine powder C was sprayed onto the surface of a diffusion magnet and placed under a vacuum of 3×10⁻⁶. -3The magnet was heated to 1000℃ and held for 4 hours in a vacuum melting furnace with a pressure of Pa. After rapid cooling to room temperature, it was removed to obtain a fully diffused magnet. The fully diffused magnet was then placed in a vacuum of 3×10⁻⁶ Pa. -3 In a vacuum melting furnace, the temperature is raised to 600℃ and held for 2 hours for annealing. After rapid cooling to room temperature, the magnet is removed to obtain target magnet #3.

[0100] The composition of diffusion source A is set to Nd by mass percentage. 95 G a10 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnet 3-1# is obtained;

[0101] The composition of diffusion source A is set to Nd by mass percentage. 50 G a50 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnet 3-2# ​​is obtained;

[0102] The composition of diffusion source B is set to Dy by mass percentage. 20 Ho5Pr 25 Ga 50 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnet 3-3# is obtained;

[0103] The composition of diffusion source B is set to Dy by mass percentage. 40 Ho 10 Pr 50 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnets 3-4# are obtained;

[0104] The composition of diffusion source C is set to Dy by mass percentage. 75 Ho5Nb 10 MO 10 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnets 3-5# are obtained;

[0105] The composition of diffusion source c is set to Dy by mass percentage. 85 Ho 15 Other process parameters and processing conditions are consistent with the preparation process of target magnet 3#, and parallel magnets 3-6# are obtained;

[0106] The performance of target magnet #3 is shown in Table 6 below.

[0107] Table 6 Performance of the original 48H magnet, target magnet #3, and various parallel magnets

[0108] 48H 18.3 14.4 51.0 - Target magnet #3 25.5 13.9 47.9 7.2 Parallel magnet 3-1# 25.4 14.0 48.1 7.1 Parallel magnet 3-2# 25.0 13.7 47.1 6.7 Parallel magnet 3-3# 24.5 13.7 47.2 6.2 Parallel magnets 3-4# 25.2 13.9 47.9 6.9 Parallel magnet 3-5# 25.4 14.0 48.2 7.1 Parallel magnet 3-6# 25.5 13.7 47.0 7.2

[0109] Example 4

[0110] The only difference between this embodiment and Embodiment 1 is that:

[0111] Diffusion source fine powder A is sprayed onto the surface of the diffusion substrate and placed under a vacuum of 2×10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 800℃ and held for 20 hours. After being rapidly cooled to room temperature, the magnet was removed to obtain the initial diffusion magnet.

[0112] The fine powder B from the diffusion source was sprayed onto the surface of the initial diffusion magnet, and then placed under a vacuum of 3 × 10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature is raised to 900℃ and held for 2 hours. After being rapidly cooled to room temperature, the magnet is removed to obtain a re-diffusion magnet.

[0113] The fine powder C of the diffusion source was sprayed onto the surface of the diffusion magnet and placed under a vacuum of 3×10⁻⁶. -3 In a vacuum melting furnace with a pressure of Pa, the temperature was raised to 900℃ and held for 4 hours. After rapid cooling to room temperature, the magnet was removed to obtain a fully diffused magnet. The fully diffused magnet was then placed in a vacuum of 3×10⁻⁶ Pa. 3 In a vacuum melting furnace, the temperature is raised to 400℃ and held for 10 hours for annealing.

[0114] Example 5

[0115] The only difference between this embodiment and Embodiment 1 is that:

[0116] Diffusion source fine powder A is sprayed onto the surface of the diffusion substrate and placed under a vacuum of 5×10⁻⁶. -3 In a vacuum melting furnace of Pa, the temperature was raised to 850°C and held for 4 hours. After being rapidly cooled to room temperature, the magnet was removed to obtain the initial diffusion magnet.

[0117] The fine powder B from the diffusion source was sprayed onto the surface of the initial diffusion magnet and placed under a vacuum of 3 × 10⁻⁶. 3 In a vacuum melting furnace of Pa, the temperature is raised to 850°C and held for 10 hours. After being rapidly cooled to room temperature, the magnet is removed to obtain a re-diffusion magnet.

[0118] The fine powder C of the diffusion source was sprayed onto the surface of the diffusion magnet and placed under a vacuum of 3×10⁻⁶. -3 In a vacuum melting furnace with a pressure of Pa, the temperature was raised to 950℃ and held for 3 hours. After rapid cooling to room temperature, the magnet was removed to obtain a fully diffused magnet. The fully diffused magnet was then placed in a vacuum of 3 × 10⁻⁶ Pa. -3 In a vacuum melting furnace, the temperature is raised to 500℃ and held for 1 hour for annealing.

[0119] Tests showed that the performance of the magnets obtained in Examples 4 and 5 was basically similar to that in Example 1.

[0120] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0121] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the described embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims.

Claims

1. A method for strengthening NdFeB magnets through grain boundary diffusion, characterized in that, include: A first diffusion source is provided and applied to the surface of a neodymium iron boron magnet, followed by low-temperature grain boundary diffusion treatment; The chemical formula of the first diffusion source is RE1 a RE2 b M 100-a-b In this context, RE1 is selected from any one or more combinations of terbium, dysprosium, and holmium; RE2 is selected from any one or more combinations of lanthanum, cerium, praseodymium, neodymium, and samarium; and M is selected from any one or more combinations of magnesium, aluminum, cobalt, copper, and gallium, satisfying 0≤a≤5 and 50≤b≤95. The process conditions for the low-temperature grain boundary diffusion treatment include: a diffusion temperature of 800~900℃, a holding time of 4~20h, and a vacuum degree not exceeding 1×10⁻⁶. -2 Pa; A second diffusion source is provided and applied to the surface of a NdFeB magnet that has undergone low-temperature grain boundary diffusion treatment, followed by medium-temperature grain boundary diffusion treatment; the chemical formula of the second diffusion source is RE1. m RE2 n M 100-m-n RE1 is selected from any one or more combinations of terbium, dysprosium, and holmium; RE2 is selected from any one or more combinations of lanthanum, cerium, praseodymium, neodymium, and samarium; M is selected from any one or more combinations of magnesium, aluminum, cobalt, copper, and gallium, and satisfies 25≤m≤50 and 25≤n≤50; the process conditions for the intermediate-temperature grain boundary diffusion treatment include: diffusion temperature of 850~950℃, holding time of 2~10h, and vacuum degree not exceeding 1×10⁻⁶. -2 Pa; A third diffusion source is provided and applied to the surface of a NdFeB magnet that has undergone intermediate-temperature grain boundary diffusion treatment, followed by high-temperature grain boundary diffusion treatment; the chemical formula of the third diffusion source is RE1. i RE2 j NRE q Among them, RE1 is selected from any one or more combinations of terbium, dysprosium, and holmium; RE2 is selected from any one or more combinations of lanthanum, cerium, praseodymium, neodymium, and samarium; NRE is selected from any one or more combinations of tungsten, molybdenum, niobium, tantalum, vanadium, and zirconium, and satisfies i≥80, 0≤j≤10, 0≤q≤10, and i+j+q=100; the process conditions for the high-temperature grain boundary diffusion treatment include: diffusion temperature of 900~1000℃, holding time of 2~4h, and vacuum degree not exceeding 1×10 -2 Pa; NdFeB magnets subjected to high-temperature grain boundary diffusion treatment are annealed to obtain grain boundary-strengthened NdFeB magnets. The annealing process conditions include: annealing temperature of 400~600℃, holding time of 1~10h, and vacuum degree not exceeding 1×10⁻⁶. -2 Pa.

2. The method according to claim 1, characterized in that, The preparation method of the first diffusion source, the second diffusion source or the third diffusion source includes: preparing raw materials according to the corresponding mass percentage, and smelting alloys in a rapid solidification furnace, making the obtained rapid solidification flakes into hydrogen-crushed coarse powder by hydrogen crushing, and then grinding the hydrogen-crushed coarse powder by air jet milling to obtain fine powder with a particle size distribution of 2~50µm, thereby obtaining the first diffusion source, the second diffusion source or the third diffusion source.

3. The method according to claim 1, characterized in that, include: The first diffusion source, the second diffusion source, or the third diffusion source is applied to and attached to the surface of the neodymium iron boron magnet by at least one of the following methods: spraying, slurry impregnation, or screen printing.

4. The method according to claim 1, characterized in that: The amount of the first diffusion source attached to the surface of the neodymium iron boron magnet is 1~3%.

5. The method according to claim 1, characterized in that: The amount of the second diffusion source attached to the surface of the neodymium iron boron magnet is 1~2%.

6. The method according to claim 1, characterized in that: The amount of the third diffusion source attached to the surface of the NdFeB magnet is 0.3~0.8%.

7. The method according to claim 1, characterized in that... The neodymium iron boron magnet is a sintered neodymium iron boron magnet with a thickness of 2~15mm.

8. A grain boundary strengthened NdFeB magnet prepared by the method of any one of claims 1-7.

Citation Information

Patent Citations

  • Method for inducing heavy rare earth elements to diffuse along crystal orientation

    CN116230382A

  • High-coercivity mixed rare earth permanent magnet material based on multi-step diffusion method and preparation method of high-coercivity mixed rare earth permanent magnet material

    CN117219431A